Variação sazonal de alguns parâmetros físicos e químicos em três rios pertencentes a uma bacia de drenagem na região centro-sul do Estado do Paraná, Sul do Brasil - Krupek, Rogério Antônio [UNESP]; Branco, Ciro Cesar Zanini [UNESP]; Peres, Cleto Kaveski [UNESP] (Universidade Estadual de Maringa, 2008)
Three small rivers belonging to the Rio das Pedras basin, located in the mid-southern region of Paraná state, were studied in order to evaluate the seasonal variation pattern of some physical and chemical parameters. Monthly samplings were carried out from April 2004 to March 2005. The following limnological parameters were measured: water temperature, specific conductance, oxygen saturation, pH, turbidity, current velocity and depth. The waters of the Rio das Pedras basin presented very peculiar characteristics, showing typical seasonal patterns for some of the studied limnological variables. An Analysis of Variance (Anova) showed significant differences only for pH and depth among streams. A Principal Component Analysis (PCA) showed a weak tendency to form groups based on seasons instead of sampling sites. The results, in general, indicate that temporal variations of the environmental parameters analyzed were not sufficient to draw a clear seasonal pattern in the Rio das Pedras basin. Most likely, the lack of an obvious seasonal pattern has been provoked by a particular regional precipitation regime, where rains are frequent and well-distributed throughout the year.
Seasonal variation in some physical and chemical parameters of three rivers belonging to a drainage basin in the mid-southern region of Paraná state, southern Brazil
Keywords: Drainage basin; Physical and chemical variables; Seasonal variation; Stream